O comportamento de compra compulsiva: um estudo com métodos neurocientíficos - Magalhães, Maria dos Remédios Antunes (2013)
The objective of this study was to analyze the association between decision making and emotional reactions in compulsive shoppers (CS) and non-compulsive shoppers (NCS). Evaluating decision making associated with emotional reactions involved in the process are unknown when comparing studies between CS and NCS groups in relation to impulse buying. The sample consisted of 35 consumers, divided among 25 compulsive shoppers (CS) and 10 non-compulsive shoppers (NCS). The methodological procedures were based on the analysis of decision making and emotional reactions detected by Electrodermal Activity (EDA / SCR), while participants performed the task presented in the decisional evaluation Iowa Glambing Task - IGT. The results of this study show a significant difference in decision making between CSs and NCSs, which correlates with the overall net score on the IGT task. These findings are suggestive of the occurrence of an impulsive cognitive style from the CSs compared to NCSs in regards to the ability of decision making by choosing disadvantageous choices in order to obtain more immediate gains. The results of Electrodermal Activity (EDA / SCR) revealed that the group of NCSs had higher scores on the magnitude scale of SCRs in advantageous choices, which reveals an emotional bond to the CNCs with pre-advantageous choices. Unlike the pattern of responses from the group of CSs, the members of NCSs show no emotional conflict and no significant somatic state when faced with choices during the IGT task. This suggests that in this particular sample, all the situations are equivalent for NCS individuals. The results obtained in this research will enable the study of factors that may represent the vulnerability of compulsive shoppers, contributing to the development of frameworks about behavior of the consumer and cognitive impairment, which deserve attention from Marketing and Psychology areas and prevention interventions in public policy.